Increased erythrocyte resistance to osmotic lysis in the acute hepatitis caused by true hepatotropic viruses non-A, non-B (nanb) - Durgawale, Pushpa; Shukla, P. S.; Mishra, Sonali (Indian journal of clinical biochemistry, 1999)
An unexpected increase in erythrocyte osmotic resistance during viral hepatitis in two patients prompted study of effects of hepatitis (in Karad) on osmotic resistance. The test was performed by placing erythrocytes in saline solutions of decreasing osmolarity and osmotic fragility defined in terms of the saline concentration at which hemolysis begins. Study included 44 infected subjects (acute viral hepatitis non-A non-B). All forty four infected subjects showed abnormal results when compared to normal subjects. increased erythrocyte osmotic resistance i.e. hemolysis begins between 0.45% to 0.40% of NaCl and is completed between 0.25% to 0.20% NaCl, whereas in normal subjects. hemolysis begins between 0.50% to 0.45% NaCl and is completed between 0.35% to 0.30% NaCl. Osmotic resistance was observed with increase in total bilirubin (mean±SD) (4.6 ±3.6), direct bilirubin (3.0±2.5), SGOT (58.8±55.5) SGPT (114.2±150.3) activity. Physiologic shifts in erythrocyte osmotic resistance may be due to changes in membrane lipid ratio.